2014
DOI: 10.1089/aid.2014.0124
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Dynamics of HIV-1 Chemokine Receptor Usage in a Multidrug-Resistant Adolescent

Abstract: Maraviroc (MVC) is licensed in clinical practice for patients with R5 virus and virological failure; however, in anecdotal reports, dual/mixed viruses were also inhibited. We retrospectively evaluated the evolution of HIV-1 coreceptor tropism in plasma and peripheral blood mononuclear cells (PBMCs) of an infected adolescent with a CCR5/CXCR4 Trofile profile who experienced an important but temporary immunological and virological response during a 16-month period of MVC-based therapy. Coreceptor usage of biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Because of the very limited therapeutical options, we added MVC to target residual R5 variants and maximize the antiviral activity of OBR. 15 Case 2 viremia reached values permanently < 100 copies/mL from week 4. A transient virological rebound was observed between week 24 and 34 (3690 copies/mL), correlating with ENF interruption because of reduced tolerance.…”
Section: Resultsmentioning
confidence: 89%
“…Because of the very limited therapeutical options, we added MVC to target residual R5 variants and maximize the antiviral activity of OBR. 15 Case 2 viremia reached values permanently < 100 copies/mL from week 4. A transient virological rebound was observed between week 24 and 34 (3690 copies/mL), correlating with ENF interruption because of reduced tolerance.…”
Section: Resultsmentioning
confidence: 89%
“…Antiviral effects of Maraviroc were investigated on U87.CD4 cells expressing wild type or chimeric CCR5 and CXCR4. Furthermore, a direct influence of the drug was observed on the onset of resistance in infected patients [24]. Phase II clinical studies confirmed the susceptibility to Maraviroc of dual mixed tropic viruses, with an activity even higher than that recorded towards pure R5 strains [25].…”
Section: Ccr5 and Cxcr4 Antagonistsmentioning
confidence: 99%